Association between genetic variants (rs920778, rs4759314, and rs217727) in LncRNAs and cervical cancer susceptibility in Chinese population: A systematic review and meta-analysis - Liu, Yi; Zhang, Qian; Ni, Rong (Frontiers in Genetics, 2022)
Objective: The relationship between gene polymorphisms in long non-coding RNAs (LncRNAs) and cervical cancer susceptibility has been thoroughly analyzed; however, the conclusions are inconsistent. Therefore, this systematic review and meta-analysis aimed to accurately assess the relationship between them. Method: Eligible literatures were retrieved from PubMed, Medline, China National Knowledge Infrastructure (CNKI), and WanFang databases before April 1, 2022. The odds ratios with the corresponding 95% confidence intervals were used to evaluate the strength of these relationships. Sensitivity analysis for publication bias was conducted to assess the stability and reliability of included literatures. Results: A total of 59 SNPs in 11 LncRNAs were summarized for a systematic review in this study, and then, a meta-analysis of rs920778 and rs4759314 polymorphisms in HOTAIR and rs217727 polymorphisms in H19 was conducted. The results demonstrated that rs920778 and rs4759314 polymorphisms were significantly correlated with cervical cancer susceptibility. Further subgroup analysis of rs920778 polymorphism showed that both small sample size and large sample size subgroups were associated with cervical cancer susceptibility. However, no association was found between rs217727 polymorphism and cervical cancer risk in all five genetic models. Conclusion: In conclusion, the rs4759314, rs920778, and rs217717 polymorphisms of HOTAIR and H19 may be associated with cervical cancer. However, the results should be interpreted with caution due to the limited sample and heterogeneity in this study. Large-scale and well-designed studies need to be practiced to validate our results.